Blood pressure response to exercise in table tennis varsity athletes - Cruz, A.; Santelices, O. Y. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The aim of the study was to examine changes in blood pressure during exercise and to identify blood pressure abnormalities in female and male table tennis collegiate players. Twenty-one athletes (female=8, male=13) completed the Queens College Step Test to determine their response to exercise. Systolic (SBP) and diastolic blood (DBP) pressure markers were measured before, immediately after, and 1, 2, 3-minute post (recovery) exercise. On average, SBP of female and male athletes significantly change after exercise but no significant differences were found between genders on all blood pressure variables. However, individual results revealed 48% of the players had SBPmax of < 140mmHg and one player has DBPmax of > 100mmHg suggesting blood pressure abnormalities. The findings support a similar study in Filipino collegiate racket sport players that showed evidence of irregular systolic and diastolic blood pressure responses to exercise. The current study provides further insights about the importance of exercise blood pressure markers to diagnose athletes at risk of developing hypertension or cardiovascular disease and to evaluate players' metabolic fitness. However, more research is needed particularly which blood pressure parameter would noticeably detect exaggerated blood pressure response to exercise in athletes.